Investigation of the effects of wing membrane slackness on thrust generation - Chua, Jasper Dong Qiu (2016)
Throughout history, mankind have been looking to the skies and have been fascinated by animals that have the ability to fly. One such animal that have been drawing greater interest in recent years are bats, the only known mammal capable of flight. In one recent study, it was found that bats have tiny muscles within their wing membranes which allow them to change the slackness of their wing membranes during flight. The theory for flapping wing aerodynamics is that, by increasing the angle of attack of the wing, the wing is able to achieve an increasing lift coefficient and in turn a larger lift force until a maximum is reached. In this experiment, the author aims to recreate this phenomenon, creating wings of varying slackness in an attempt to study if this phenomenon is a viable form a wing control for flapping wing micro-aerial vehicles (MAV).